EFEKTIVITAS CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK - Chotijah, Siti; Susanto, Andi (Institut Agama Islam Negeri (IAIN) Tulungagung, 2019)
The purpose of this research is comparing the conceptual understanding of students who learn with Contextual Teaching and Learning using modules in the material of Class VIII Two-Variable Linear Equation (SPLDV) System in SMP N 2 Timpeh. This study was an Quasy Experiment with a Randomized Control Group Design Only. The population of all eighth grade students of SMP N 2 Timpeh in 2018/2019 which collected 66 people. Sampling by Simple random sampling and selected class VIII students. A as experimental class and VIII. B as a control class. The results of the study, obtained an average value of students' understanding of the mathematical concepts in the experimental class and combined controls were 83.35 and 78.72. Furthermore, hypothesis testing is done for the students' ability to understand concepts, obtained that t count > t table, which states the understanding ability of students who learn through contextual Teaching and Learning using a higher module about the ability to learn concepts of students who learn through conventional learning. This shows that learning uses modules effectively in improving students' conceptual comprehension abilities.